A Preliminary Sentinel Surveillance Report on Antibiotics Resistance Trend of Streptococcus Pyogenes in Kolkata Region, India - Dipanwita Ray; Sukanta Sinha; Somnath Saha; Rathindra Nath Dutta; Sujata Bhattacharya; Nishit Kumar Pal; Basudev Bhattacharya (Al Ameen Medical College, 2010)
Streptococcus pyogenes is an important cause of serious bacterial infection in both adults and school-going children. On the present scenario of emerging changes observed in drug resistant pattern of S. pyogenes, this study was undertaken, from October2008 to July2009, to evaluate the trend of resistance pattern to various antibiotics by the Kirby-Bauer method of disk diffusion in Kolkata, India. A total of 115 isolates of S. pyogenes were identified by standard procedure. All strains were susceptible to penicillin, cephotaxime, clindamycin and vancomycin. 60 isolates were resistant to tetracycline. Four isolates have been found to be resistant to erythromycin, which is a very rare occurrence in West Bengal. This finding may be alarming for emergence of resistance against this safe drug, which may complicate the treatment of patients who are allergic to penicillin.